Drainage work / Ahmad Faris Hakim Azrin - Azrin, Ahmad Faris Hakim (Universiti Teknologi MARA, Perak, 2019)
Drainage is a system of pipework, usually installed below ground level, to convey the discharge from sanitary fittings, rainwater gutters and down pipes to a suitable disposal installation. The purpose of making this report is to determine the process of preparing drainage work in office and on site. Data and information for making this report through observation, interview, site visit and document review. The process began from the office for designing purpose before proceed to the site. After all the authorities gave their approval of design from road and drainage drawing, drainage work could began on the site as in the schedule. Throughout this project, there were a few problems occur before and during construction. Solutions have taken to overcome the problems. Based on the ponder of the case consider, it can be concluded that the strategies of development project are appeared, issues happened has been recognize and the solution is taken.